Validity E-Learning of Chemistry Learning Based on PjBL (Project Based Learning) model for Basic Chemistry Law Material with the Flipped Classroom Approach for Ten Grade High School - Rosi Efliana; Aidila Fitri; Ahmad Ziqra; Efliana Efliana; Gusnella Gusnella (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
E-learning based on Project Based Learning (PjBL) on Basic Chemistry Law material by applying the flipped classroom approach in the learning processvalidity and practicality have been determined. The type of research used is Research and Development (R&D). The development model is a 4-D model which consists of 4 stages, namely (1) Define, (2) Design, (3) Develop, (4) Desseminate. The socialization stage was not carried out due to time and cost constraints. The research instrument used was a validation questionnaire and a practicality questionnaire. The validation questionnaire was filled in by 1 chemistry lecturer from the Faculty of Mathematics and Natural Sciences UNP and 1 teacher of MAN 2 Pesisir Selatan. Data were analyzed using kappa moments. The average validity test of the kappa moment content is 0.84 with the very high validity category. The average construct validity test for the kappa moment was 0.78 in the high category. Thus, it can be concluded thate-learning based on Project Based Learning (PjBL) with the flipped classroom approach valid.